Scalable, Stereocontrolled, Total Synthesis of Carolacton - Bian, Chuan-Cai; Li, Yong-Qiang; Yang, Hao-ran; Yu, Xiao-Ming (Synthesis, 2023)
A route for the scalable, stereocontrolled, total synthesis of carolacton is presented starting from commercially available S-Roche ester, d-ribose, and a known allylic alcohol. Key transformations in the total synthesis include a [3,3]-Claisen rearrangement, Sharpless asymmetric epoxidation–methyl ring-opening, or Leighton asymmetric crotylation, Evans aldol–reductive deoxygenation, and ring closing metathesis (RCM). The total synthesis of carolacton (151 mg isolated, 9.2% overall yield) was completed in 23 linear steps. Additionally, 56 mg of the carolacton C15–C16 cis-olefin isomer was obtained.
Keywords: carolacton; total synthesis; stereocontrolled; reductive deoxygenation; RCM